2020
DOI: 10.1002/rsa.20972
|View full text |Cite
|
Sign up to set email alerts
|

Long paths and connectivity in 1‐independent random graphs

Abstract: A probability measure on the subsets of the edge set of a graph G is a 1-independent probability measure (1-ipm) on G if events determined by edge sets that are at graph distance at least 1 apart in G are independent. Given a 1-ipm , denote by G the associated random graph model. Let  1,⩾p (G) denote the collection of 1-ipms on G for which each edge is included in G with probability at least p. For G = Z 2 , Balister and Bollobás asked for the value of the least p ⋆ such that for all p > p ⋆ and all ∈  1,⩾p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(36 citation statements)
references
References 32 publications
(62 reference statements)
0
26
0
Order By: Relevance
“…In this model, each edge is open with probability p 4 + (1 − p) = 1 − 3 4 p, so p max (Z 2 ) ≥ 1 − 3 4 p site . Now, as noted in the introduction, Day, Falgas-Ravry, and Hancock [10] showed that…”
Section: Minimisementioning
confidence: 90%
See 4 more Smart Citations
“…In this model, each edge is open with probability p 4 + (1 − p) = 1 − 3 4 p, so p max (Z 2 ) ≥ 1 − 3 4 p site . Now, as noted in the introduction, Day, Falgas-Ravry, and Hancock [10] showed that…”
Section: Minimisementioning
confidence: 90%
“…The best known lower bound on both p max (Z 2 ) and lim n→∞ p max (Z n ) comes from a construction of Day, Falgas-Ravry, and Hancock in [10] which gives…”
Section: Question 2 ([2]mentioning
confidence: 99%
See 3 more Smart Citations